PENGARUH KEPEMIMPINAN KETUA ORGANISASI TERHADAP MOTIVASI KERJA ANGGOTA HIMPUNAN MAHASISWA DEPARTEMEN ILMU ADMINISTRASI NEGARA FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI PADANG - Agiezah Vella Warman; Syamsir; Fadhila Ilahi; Nadiva Betayu Ramadani; Vira Siti Hanifah; Sri Wulandari; Zakiyah Ahmad (STKIP Subang, 2026)
Leadership is a decisive element in directing organizational performance, especially in student organizations that rely on member participation. This article aims to describe the chairman’s leadership practices, identify the problems that arise, analyze their causes, and explain the solutions implemented along with recommendations for improvement. The study uses a qualitative approach with data collected through observation and interviews. The findings indicate that the chairman’s leadership style tends to be democratic, as shown by member involvement in discussion and decision-making. Nevertheless, implementation still faces several issues, including uneven member participation, unstable internal coordination, and imbalanced task distribution. These problems are influenced by differences in member commitment, inconsistent communication, and suboptimal supervision. The solutions implemented include strengthening coordination, clarifying task division, and improving communication among administrators. The article recommends participative leadership supported by firm supervision, continuous member development, and systematic evaluation to improve organizational effectiveness.